ANALISIS KINERJA PERUSAHAAN TERHADAP NILAI PERUSAHAAN: Pada Perusahaan Perdagangan Besar Yang Terdaftar Di Bursa Efek Indonesia - Widiastuti (2021)
The aim of research is to see the effect of profitability is proxied by Retrun On asset (ROA), Liquidity proxied by Current Asset (CR), and Solvency proxied by Debt Equity Ratio (DER) to Firm Value is proxied by Price Book Value (PBV). The research examines the population of wholesale sector companies listed on the Indonesia Stock Exchange (BEI) for the period 2016-2019. The sampling techniqueused in this study was purposive sampling technique with it obtained 15 wholesale sector companies with an observation period of four years in order obtain 60 sample data. The analysis used Microsoft Excel 2013 using the E-views 11 program to test the hypothesis with Pane Data Analysis and the confidance level used 5%. The result of this study partially show that, (1) Profitability has no significant effect on Firm Value, (2) Liquidity has a negative effect on Firm Value, (3) Solvency has no effect on Firm Value.